Causes and consequences of sperm mitochondrial dysfunction. (8th June 2020) - Durairajanayagam, Damayanthi; Singh, Dipty; Agarwal, Ashok; Henkel, Ralf
Abstract: Mitochondria have multiple functions, including synthesis of adenine triphosphate, production of reactive oxygen species, calcium signalling, thermogenesis and apoptosis. Mitochondria have a significant contribution in regulating the various physiological aspects of reproductive function, from spermatogenesis up to fertilisation. Mitochondrial functionality and intact mitochondrial membrane potential are a pre‐requisite for sperm motility, hyperactivation, capacitation, acrosin activity, acrosome reaction and DNA integrity. Optimal mitochondrial activity is therefore crucial for human sperm function and semen quality. However, the precise role of mitochondria in spermatozoa remains to be fully explored. Defects in sperm mitochondrial function severely impair the maintenance of energy production required for sperm motility and may be an underlying cause of asthenozoospermia. Sperm mtDNA is susceptible to oxidative damage and mutations that could compromise sperm function leading to infertility. Males with abnormal semen parameters have increased mtDNA copy number and reduced mtDNA integrity. This review discusses the role of mitochondria in sperm function, along with the causes and impact of its dysfunction on male fertility. Greater understanding of sperm mitochondrial function and its correlation with sperm quality could provide further insights into their contribution in the assessment of the infertile male.